Penerapan 3M Terhadap Pencegahan Kejadian DBD di Wilayah Puskesmas Panambungan Kota Makassar - Fransiska Lang; Muharti Syamsul; Nur Hamdani Nur (Journal of Health Quality Development, 2021)
Dengue Hemorrhagic Fever (DHF) is a contagious disease caused by the dengue virus through the bite of an Aedes mosquito. One of the causes of this DHF incident is the poor sanitation of the environment around residential areas, efforts to prevent dengue fever are breaking the transmission chain by controlling the vector through the eradication of mosquito nests (PSN) and the implementation of the 3M movement.This study aimed to determine the description of the implementation of 3M in the working area of ?? Panambungan Health Center, Makassar.The type of this research was is a quantitative study with a descriptive approach. Data collection was carried out from September to October 2020. The population was all people who live in Kel. Panambungan. Data were collected through interviews using an observation sheet and a questionnaire. In the activity of draining water reservoirs, 67 (83.8%) families conducted this activity properly, while the other 13 (16.2%) families less conducted this activity. In the activity of burying used goods, 18 (22.5%) families conducted this activity properly, while the other 62 (77.5%) families less conducted this activity. Finally, in the activity of closing water reservoirs, 24 (30.4%) families conducted this activity properly, while the other 55 (69.6%) families less conducted this activity. Based on the results of the study, it is recommended to the public to pay attention to environmental conditions to prevent the occurrence of DHF.